Enhancing Business Performance through Digital Financial Literacy: Evidence from Gorontalo - Adam, Echan; Bobihu, Nofita; Boekoesoe, Yuriko (Jurnal AGRISEP, 2025)
The digital financialization of Micro, Small, and Medium Enterprises (MSMEs) increases access to information and facilitates resource management. During the pandemic, there was a significant surge in digital transactions, increasing sales of several products, with Gorontalo Province experiencing a 3.57% rise. This research investigates the impact of social factors on digital financial literacy and their influence on the performance of MSMEs. Conducted in Gorontalo City from March to July 2024, this research employed an explanatory approach, focusing on the founders of MSMEs, specifically 50 individuals who served as respondents. Primary data was collected through structured interviews using questionnaires. The analysis utilized Structural Equation Modeling-Partial Least Squares (SEM-PLS), supported by Smart-PLS 3.0 software. The findings reveal that social factors significantly influence digital financial literacy, although they do not directly affect MSMEs' performance. Digital technology, however, has a significant impact on MSMEs' performance and mediates the relationship between social factors and performance. Despite these advancements, many MSME actors lack proper financial management practices, such as recording daily cash inflows and outflows, limiting their financial awareness. Targeted financial education programs are essential and include hands-on training on the use of financial management applications for tracking income and expenses. Furthermore, collaborations with financial institutions, fintech platforms, and e-commerce providers can facilitate training in digital financial tools and services. Although participation in such initiatives is currently limited, institutions like Bank Indonesia can scale up efforts to develop model MSMEs that inspire broader adoption of digital financial practices among other enterprises.